Efficacy of diode laser and sonic agitation of Chlorhexidine and Silver-nanoparticles in infected root canals - Abdelgawad, Latifa Mohamed; Asmail, Niven; Latif, Somia Abdel; Safaan, Ali Mohamed (Brazilian Dental Science, 2020)
Objective: To assess the efficacy of agitation of chlorohexidine (CHX) and Silver nanoparticles “AgNps” with 810nm diode laser or sonic endoactivator compared to side –vented needle on infected root canals with Enterococcus “E” Faecalis biofilms. Material and Methods: Sixty-five extracted human premolars with single oval canals were instrumented by protaper system up to F3. Biofilms of E. faecalis were generated based on a previously established protocol. Two teeth were used to check the biofilm formation, then the remaining Teeth were randomly divided into three equal experimental groups according to agitation techniques used: group 1 (810 nm diode laser with 1 watt), group 2 (sonic endoactivator) and group 3 (Side vented needle). Each group was further divided into three equal subgroups according to the irrigant solution into; subgroup A: chlorohexidine, subgroup B: silver nanoparticles and subgroup C: distilled water: Confocal laser scanning microscopy “CLSM” was used to assess bacterial viability. Data were analyzed by appropriate statistical analyses with P = 0.05. Results: Regarding the activation method, all groups had a significantly high percentage of dead bacteria (P < 0.05). However, Laser was significantly the highest and Endoactivator the least (P < = 0.001). Diode laser agitation of AgNps irrigant showed the highest reduction percentage of bacteria (78.1%) with a significant difference with both CHX and water irrigation, Conclusion: Under the condition of the present study; results reinforced that laser activation is a useful adjunct, 810 nm diode laser agitation of AgNps or chlorhexidine was more effective in disinfection of oval root canals than endoactivator and side vented needle techniques.KeywordsDentinal infection; Silver-nanoparticles; chlorohexidine; agitation; Diode Laser; Sonic endoactivator.